Prevalence of Disordered Eating Among International Sport Lead Rock Climbers - Joubert, Lanae M.; Gonzalez, Gina Blunt; Larson, Abigail J. (Frontiers in Sports and Active Living, 2020)
Disordered eating (DE) is characterized as a range of irregular eating patterns or behaviors, which may lead to pathological eating or a clinical eating disorder diagnosis. DE patterns are associated with a variety of negative health outcomes. The prevalence of DE is highest in female athletes who participate in aesthetic or weight dependent sports. Elite rock climbers tend to be strong, small and lean, but the prevalence of DE in rock climbers is unknown. The purpose of the present study was to assess DE prevalence in a large group of international rock climbers and to explore the relationship between sport rock climbing ability and DE. A web-based survey assessed both DE (Eating Attitudes Test-26) and climbing ability based on the International Rock Climbing Research Association’s position statement on comparative grading scales. The survey was distributed to international climbing communities; 810 individuals attempted the survey; 604 completed all questions; 498 identified as sport lead climbers. The majority of sport lead climbers were lower grade/intermediate (57.8%), compared to advanced (30.7%) and elite/higher elite (11.4%), and male (76.9%). Forty-three sport lead climbers reported a score of 20 or above on the EAT-26 indicating an 8.6% prevalence of DE in this sample. Male climbers had a DE prevalence of 6.3% (24 of 383) and female climbers more than doubled that with 16.5% (19 of 115). Chi-square analysis revealed that DE was associated with climbing ability level [χ2 (2, n = 498, 8.076, p = 0.02)], and when analyzed by sex, only the female climbers had a significant relationship of DE with climbing ability [χ2 (2, n = 115, 15.640, p = 0.00)]. These findings suggest sport lead rock climbers are not immune to DE and that the risk is elevated in female climbers, particularly at the elite/high elite climbing ability level. Our research indicates further investigations are warranted to determine if and how disordered eating behaviors affect health and performance of adult rock climbers.